Employment-related difficulties and distressed living condition in patients with hepatitis B virus: A qualitative and quantitative study - Taeko Oka; Hiroaki Enoki; Yukari Tokimoto; Teruaki Kawanishi; Meguru Minami; Takahiro Okuizumi; Kiyohiko Katahira (BMC, 2017)
Abstract Background In Japan, an estimated 400,000 people have the hepatitis B virus (HBV), many of whom were infected as a result of group vaccinations. People with HBV face many challenges, including disease progression, employment-related difficulties, and increased medical expenses. The relationship between HBV victims' daily life suffering and poverty associated with HBV-related employment changes has not been examined. We aimed to clarify the employment-related hardships experienced by Japanese HBV victims, and the relationships between these hardships and daily life suffering, including poverty, through qualitative and quantitative analyses. Methods The study population comprised 11,046 people infected with HBV via group vaccination who filed lawsuits in Japan's District Courts by 2014. First, we conducted a qualitative study (2013) using the KJ method, with 107 participants (68 men, mean age 58.9 years; 39 women, mean age 55.3 years). Semi-structured interviews were conducted covering participants' current condition, treatment, medical expenses, and life difficulties (employment- and family-related problems). In 2014, we conducted a quantitative study. We mailed questionnaires to the entire study population, investigating the topics covered in the interviews (response rate 60.1%). Daily life suffering was determined by responses to the question "What do you think about your everyday life situation?" We performed binomial logistic regression analyses to verify the relationships between daily life suffering and disease, employment, and income status. Results Interview data were integrated into seven islands: intention to work, lack of understanding of HBV in the workplace, inability to buy life insurance, burden due to medical expenses, life failure, dissatisfaction with the system, and wishing for life balance. The quantitative analyses showed significant positive correlations between daily life suffering and liver cancer (odds ratio [OR] 1.47, 95% confidence interval [CI]: 1.00-2.17, p < 0.05), being a part-time/casual employee (OR 1.46, 95% CI: 1.11-1.92 p < 0.01), and an income below the national average (p < 0.01). Conclusion We qualitatively and quantitatively demonstrated that employment-related hardships and daily life suffering are prevalent in people with HBV. Their likelihood of experiencing distress in daily life increases with increasing medical expenses, insecure employment status (e.g., job loss) attributable to HBV, and the resulting poverty.